CULTURAL CONFLICT EXPERIENCED BY THE CENTRAL CHARACTER IN THE NOVEL CRAZY RICH ASIAN BY KEVIN KWAN - Eva Monica; Ni Made Widisanti S; Sari Rejeki (Universitas Pakuan, 2020)
Cultural conflict can occur because the diversity of cultures, religions, and races. When we refuse to learn about other cultures, stereotype, misinterpretation and tendency to change attitudes toward other ethnicity might happen. The purposes of this thesis is to explore the cultural conflict and the settlement in Kevin Kwans novel Crazy Rich Asian. This novel presents Rachel Chu and Nicholas Young as the central character. The research is conducted by means of descriptive analysis method. The results shows that the cultural conflicts experienced by Rachel and Nick were caused by stereotypes, misunderstandings, ethnocentrism and materialism, a high sense of selfishness that made the conflict continue without any resolution.Keywords: Crazy Rich Asian; Cultural Conflict; Culture.